MOVEMENTS AND MORTALITY OF PEN RAISED WILD TURKEYS RELEASED ON A HUNTING PRESERVE - Edward K. Brown; Douglas L. Gilbert (Wildlife Society Bulletin)
Abstract Spring and summer minimum home ranges of radiotelemetry instrumented turkeys (Meleagris gallopavo silvestris) released at Rachelwood Wildlife Research Preserve averaged 288 ha and 309 ha respectively. Mean maximum linear distance traveled for 6 instrumented hens was 3.0 km. Fifty and 75% areas of activity averaged only 21 and 47% of spring and summer range size, respectively. Differences between spring and summer range sizes and movements were nonsignificant. All nests of instrumented hens were located inside the preserve. Predators destroyed five or six nests of instrumented hens. Brood range size for one hen was very restricted and did not increase over the summer. Between 1972 and 1975, only 14% of all leg bands from turkeys returned to Rachelwood were recovered outside the preserve. Considerations found to be important in evaluating dispersal of wild turkeys were: (1) availability of supplemental feed within a turkey's seasonal range, (2) amount and arrangement of favorable turkey habitat inside the preserve, and (3) survival rates of released turkeys.